SELEKSI BAKTERI POTENSIAL PENGHASIL ENZIM HIDROLITIK DARI SAMPEL TANAH TEMPAT PEMBUANGAN AKHIR BUKIT PINANG SAMARINDA - Admaja, Junior Try; Astuti, Winni; Kartika, Rudi (Jurusan Kimia FMIPA UNMUL, 2024)
Bacteria are one of the microorganisms that have the potential to produce hydrolytic enzymes. This research was carried out to isolate bacteria from the soil of the Bukit Pinang Samarinda Final Disposal Site and select bacteria that produce cellulase, protease and lipase enzymes. Bacteria from landfill soil were isolated using the spread plate method and 10 single colony bacterial isolates were selected which were then coded TPA 1 – TPA 10. The results of the selection of bacteria producing hydrolase enzymes showed that 9 isolates were capable of producing protease enzymes, 6 isolates were capable of producing cellulase enzymes and 4 isolates were capable of producing cellulase enzymes. The isolate was able to produce the lipase enzyme.